Caregivers' Knowledge and Use of Fermented Foods for Infant and Young Children Feeding in a Rural Community of Odi, Gauteng Province, South Africa - Paul K Chelule; Mathildah M Mokgatle; Lindiwe I Zungu; Armelia Chaponda (Tabriz University of Medical Sciences, 2014)
Background: Fermented foods have positive health effects in adults and children if consumed regularly. However, lack of knowledge and perceptions to-wards fermented foods may limit their usage. This study aimed to assess the caregivers' awareness and usage of fermented foods for feeding children in peri-urban/rural communities of Gauteng Province. Methods: A qualitative exploratory study was conducted in June, 2012, in a peri-urban/rural community to assess the awareness and use of fermented foods by child caregivers attending a local antenatal clinic through focus group discussions. Results: Thirty three caregivers participated in the study; however 29 indicated their demographic profiles. Four major themes that emerged from the analysis included knowledge on fermented foods, perceived benefits of fermentation, varied views about fermentation and feeding practices. Fermented foods that caregivers, their families and community members consume include ting, fat cakes, dumplings, sorghum beer and mageu. Findings also showed that children consumed fermented foods in form of soft ting porridge; and yoghurt, marketed as Activia and Danone commercial brands. Also, caregivers were not comfortable feeding their children with fermented foods, indicating their limited knowledge on the nutritional value of these foods. Conclusion: It is critical to promote caregivers' knowledge and use of fermented foods for feeding infants and young children in South African rural communities.